GUARANTEES OF HUMAN AND CITIZEN RIGHTS AND FREEDOMS IN THE CONSTITUTION THEORETICAL ANALYSIS - Mirzo, Khalilov Shokhrukh (PT ANTIS International Publisher, 2024)
The article presents the concept and significance of guarantees of human and citizen rights and freedoms, the state's provision of rights and freedoms, the protection of rights and freedoms through the courts, as well as thoughts and theoretical analyses regarding guarantees of equal rights between women and men, and scientific observations.